2021
DOI: 10.1186/s12889-021-11326-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and initial spatiotemporal visualisation of COVID-19 in a major city in the Middle East

Abstract: Background The Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) emerged initially in China in December 2019 causing the COVID-19 disease, which quickly spread worldwide. Iran was one of the first countries outside China to be affected in a major way and is now under the spell of a fourth wave. This study aims to investigate the epidemiological characteristics of COVID-19 cases in north-eastern Iran through mapping the spatiotemporal trend of the disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…With respect to COVID-19 vaccination, it is vital to prioritise the elderly population as it well known that higher age increases the risk of mortality [ 37 , 38 ]. In this study, we measured the PSA to vaccination centres by developing a modified version of the E2SFCA model using a weighted population classified by age structure in each geographical area, as this enhancement should generate more realistic results for healthcare decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to COVID-19 vaccination, it is vital to prioritise the elderly population as it well known that higher age increases the risk of mortality [ 37 , 38 ]. In this study, we measured the PSA to vaccination centres by developing a modified version of the E2SFCA model using a weighted population classified by age structure in each geographical area, as this enhancement should generate more realistic results for healthcare decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial patterns of COVID-19 incidence were investigated by census level with addressing the epidemiological features, during the first wave of the pandemic in Mashhad, Iran [ 10 ]. In that study, hotspots and high/low-risk areas were detected by using the Getis-Ord Gi* and Local Moran’s I statistic [ 11 , 12 ].…”
Section: Objectivementioning
confidence: 99%
“…6 In this context, several studies using spatiotemporal analysis tools have demonstrated the impact of morbidity, mortality, and geographic spread of COVID-19 worldwide. [7][8][9][10] Importantly, a study carried out in the United States identified COVID-19 spatiotemporal clusters, which were classified as priority areas for resource allocation and implementation of diseasecontrol measures. 11 Likewise, studies assessing the spatiotemporal patterns of COVID-19 have been developed extensively in Brazil.…”
Section: Introductionmentioning
confidence: 99%